Preparing for climate change and hazards: Individual houseowners trust in local authorities and private entrepreneurs. (December 2019) - Kolmodin, Sophie; Lundgren, Minna; Andersson, Caroline
Abstract: A changing climate that entails a growing number of hazards poses a challenge to communities across the world. Particularly exploited areas in mountain and maritime zones have become increasingly vulnerable. Homeowners in such areas has been identified as key actors in the pursuit of robust communities, though large groups of people tend to trust mainly in the risk management of local authorities. In order to achieve a better understanding in how individual homeowners address risks related to their properties and the ways in which they put their trust in the risk management in different actors, not only public authorities, we conducted interviews with homeowners in Sweden's largest ski resort, Åre, in recent years affected by an increasing number of landslides. The empirical findings show that households have different targets of trust during different stages of a crisis, which also aligns with previous research. While the respondents worried about the overall development in the area, their main concerns were related to their properties and how a harsher climate would affect their economic value. The homeowners furthermore expressed that their trust in the municipality and the local entrepreneur that runs the ski resort is low when it comes to crisis management. Yet rural populations in general are used to handle crises on their own, as assistance from authorities usually takes longer time. It is thus important that the municipality and local entrepreneurs assume responsibility not to jeopardize sustainability in future exploitations in the area in order to establish trust in relation to local homeowners.